A frog in boiling water? A qualitative analysis of psychiatrists' use of metaphor in relation to psychological trauma. (December 2020) - Isobel, Sophie; McCloughen, Andrea; Foster, Kim
Objective: Tensions about the definition, diagnostics, and role of psychological trauma in psychiatry are long-standing. This study sought to explore what metaphor patterns in qualitative interviews may reveal about the beliefs of psychiatrists in relation to trauma. Method: A qualitative inquiry using systematic metaphor analysis of 13 in-depth interviews with Australian psychiatrists. Results: Three themes were identified: a power struggle between people, trauma, and psychiatry; trauma is not a medical condition; and serving the profession to protect society. Conclusions: Metaphors present trauma as a powerful force that people can manage in different ways. Psychiatrists may view trauma as a social rather than medical issue. Psychiatrists experience role pressure associated with trauma including incongruence with risk management expectations of their roles.